The effect of BCAA supplementation upon the immune response of triathletes - Bassit, R. A.; Sawada, L. A.; Bacurau, R. F.; Navarro, F.; Costa-Rosa, L. F. (Medicine & Science in Sports & Exercise, 2000)
Introduction: Intense long-duration exercise could lead to immune suppression through a decrease in the circulating level of plasma glutamine. The decrease in plasma glutamine concentration as a consequence of intense long-duration exercise was reversed, in some cases, by supplementing the diet of the athletes with branched-chain amino acids (BCAA). To better address this question, we have evaluated some blood parameters (lymphocyte proliferation, the level of plasma cytokines, plasma glutamine concentration, and in vitro production of cytokines by peripheral blood lymphocytes) before and after the São Paulo International Triathlon, as well as the incidence of symptoms of infections between the groups. Methods: Twelve elite male triathletes of mean age 25.5 ± 3.2 yr (ranging from 21.4 to 30.1 yr), weighing 74.16 ± 3.9 kg, swam 1.5 km, cycled 40 km, and ran 10 km (Olympic triathlon) in the São Paulo International Triathlon held in April 1997 and April 1998. In both events, six athletes received BCAA and the others, placebo. Results: Athletes from the BCAA group (BG) presented the same levels of plasma glutamine, before and after the trial, whereas those from the placebo group showed a reduction of 22.8% in plasma glutamine concentration after the competition. Changes in the proliferative response of peripheral blood lymphocytes were accompanied by a reduction in IL-1 production after exercise (22.2%), which was reversed by BCAA supplementation (20.3%), without changes in IL-2 production. Discussion: The data obtained show that BCAA supplementation can reverse the reduction in serum glutamine concentration observed after prolonged intense exercise such as an Olympic triathlon. The decrease in plasma glutamine concentration is paralleled by an increased incidence of symptoms of infections that results in augmented proliferative response of lymphocytes cultivated in the absence of mitogens. The prevention of the lowering of plasma glutamine concentration allows an increased response of lymphocytes to ConA and LPS, as well as an increased production of IL-1 and 2, TNF-[alpha], and IFN-[gamma], possibly linked to the lower incidence of symptoms of infection (33.84%) reported by the supplemented athletes.